UV-curable polyurethane resin containing side double bond itaconic polyol and application of UV-curable polyurethane resin
By using side double-bonded itacang polyol in UV curing resin, the problems of uncontrolled double bond content and diluent safety hazards are solved, and the adjustability and environmentally friendly characteristics of double bond content are achieved, meeting the material performance needs of complex engineering structures.
Patent Information
- Application Number
- CN202510150692.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-05-02
AI Technical Summary
Due to the uncontrollable double bond content of existing UV cured resins, they cannot fully meet the strict demands of complex engineering structures for material performance. At the same time, the addition of small molecule active diluents poses safety risks and environmental pollution risks.
The preparation method of side double bond itacang polyol is adopted to synthesize itacang acid, allyl glycidyl ether, catalyst and polymerization inhibitor in an inert gas atmosphere to obtain double bond-rich side double bond itacang polyol, and add it to the UV-curable polyurethane resin to adjust its doping amount to adjust the content of double bonds in the resin.
It realizes the adjustability of double bond content, meets application needs in different fields, avoids safety hazards and environmental pollution of adding diluents, and has environmentally friendly characteristics.
Smart Images

Figure CN119912331A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of UV curing technology, and in particular to a UV curable polyurethane resin containing a side double-bond itaconate polyol and an application thereof. Background Art
[0002] In the field of photocuring technology, UV curing process has occupied a dominant position with its outstanding advantages such as high efficiency, high economy, environmental friendliness and wide applicability. It has become the most widely used technical process and is respected as a pioneering new green industrial technology benchmark in the 21st century.
[0003] At present, the UV-curable resins used in various fields include unsaturated polyesters, epoxy acrylates, polyurethane acrylates, polyester acrylates, and pure acrylic resin oligomers. Among them, the double bonds of unsaturated polyesters are present on the main chain structure. This unique distribution pattern makes the main chain double bonds show lower reactivity. To make up for this defect, it is often necessary to introduce active diluents to optimize its curing performance. Secondly, as far as pure acrylic resin is concerned, although its double bonds are located in the side chain, its preparation process is highly dependent on grafting reactions. This synthesis path is prone to significant fluctuations in the double bond content, which is difficult to accurately control, limiting its performance in some fine applications with high stability requirements. As for other common UV-curable resins, double bonds are usually concentrated at the terminal groups of oligomers, making it difficult to achieve an optimized combination of high strength and high toughness at the same time. The above-mentioned UV-curable resins cannot fully meet the stringent demands of complex engineering structures for material performance due to their uncontrollable double bond content.
[0004] In response to the problems existing in the above-mentioned UV-curable resin products, small molecule active diluents are often added to coordinate the curing process in their actual use. However, these active diluents themselves have many disadvantages. On the one hand, active diluents have a strong pungent odor and are very easy to volatilize and dissipate into the surrounding environment during use, which not only causes direct pollution load to the ecological environment, but also poses a potential threat to the health of operators; on the other hand, the introduction of active diluents may also interfere with the original stable chemical structure of the resin to a certain extent, and have a negative impact on the comprehensive performance of the resin, such as reducing key indicators such as durability and impact resistance of the material, and weakening the reliability of the product under complex working conditions. Therefore, it is of great significance to develop an environmentally friendly and green UV-curable resin with side chain double bonds and adjustable double bond content, which does not contain active diluents. Summary of the invention
[0005] In view of this, the purpose of the present application is to provide a UV-curable polyurethane resin containing side double-bond itacon polyols and its application, which is used to solve the problem that the existing UV-curable polyurethane resin has a limited application range due to the unadjustable double chains, and the safety hazards aggravated by the addition of diluents during the application process.
[0006] In order to achieve the above technical purpose, the present application provides a method for preparing a side double-bond itacon polyol, comprising the following steps:
[0007] Step S1, 60-70 parts of itaconic acid, 100-120 parts of allyl glycidyl ether, 0.08-0.15 parts of a catalyst and 0.08-0.15 parts of a polymerization inhibitor are mixed uniformly in an inert gas atmosphere, and kept warm for reaction at 95°C-110°C for 1.5-2 hours to obtain a crude product;
[0008] Step S2, taking the crude product and distilling it under reduced pressure at 100-110° C. for 0.5-1 h to obtain itacon polyol with a side double bond.
[0009] Furthermore, the catalyst includes one of tetrabutylammonium bromide, benzyltriethylammonium chloride, triphenylamine, triethylamine, tributylamine and the like.
[0010] Furthermore, the polymerization inhibitor includes a phenolic polymerization inhibitor and a quinone polymerization inhibitor; the phenolic polymerization inhibitor includes one of p-methoxyphenol and hydroquinone; the quinone polymerization inhibitor includes one of p-benzoquinone and tetrachlorobenzoquinone.
[0011] The present application provides a UV-curable polyurethane resin, comprising 99.5 to 99.9 parts of a polyurethane resin and 0.1 to 0.5 parts of a photoinitiator;
[0012] The polyurethane resin is composed of the following components in parts by mass: 40-80 parts of oligomer polyol; 5-25 parts of lateral double-bond itacon polyol prepared according to any one of claims 1 to 3; 10-30 parts of isocyanate; 0.1-1 parts of catalyst; 0.1-1 parts of inhibitor; 3-4 parts of end-capping agent; and 30-50 parts of solvent.
[0013] Further, the oligomer polyol includes one or more of polybutylene adipate diol, polypropylene carbonate diol, polypropylene glycol and polycaprolactone diol.
[0014] Further, the isocyanate includes one or more of isophorone diisocyanate, diphenylmethane diisocyanate, meta-xylylene diisocyanate, toluene diisocyanate, hexamethylene diisocyanate and dicyclohexylmethane diisocyanate.
[0015] Further, the solvent includes one or more of ethyl acetate, dimethylformamide, toluene, acetone and tetrahydrofuran.
[0016] Further, the end-capping agent includes one or more of ethanol, n-propanol, hydroxyethyl acrylate and hydroxyethyl methacrylate.
[0017] Furthermore, the catalyst includes one or more of stannous isooctanoate and stannous octoate.
[0018] The present application provides an application of a UV-curable polyurethane resin for preparing UV viscosity-reducing adhesive, UV-curable coating, and UV-curable electronic packaging adhesive.
[0019] In summary, the present application provides a method for preparing a lateral double-bond itaconic polyol, which is synthesized by heating itaconic acid, allyl glycidyl ether, a catalyst and an inhibitor under an inert gas atmosphere. Based on the above-synthesized lateral double-bond itaconic polyol, the present application also provides a UV-curable polyurethane resin containing lateral double-bond itaconic polyol, which precisely regulates the amount of lateral double-bond itaconic polyol to adjust the content of double bonds in the UV-curable polyurethane resin, so that it can meet the application needs of different fields. The UV-curable polyurethane resin provided in the present application can be applied to fields such as UV viscosity-reducing adhesives, UV-curing coatings and UV-curing encapsulating adhesives, especially when the UV-curable polyurethane resin is used to prepare UV viscosity-reducing adhesives, it can take into account the characteristics of "strong bonding before illumination and viscosity reduction after illumination curing"; in addition, the UV-curable polyurethane resin does not need to add small molecule diluents during the application process, avoiding a series of safety hazards caused by diluents, and has environmentally friendly characteristics. Compared with the prior art, the UV-curable polyurethane resin provided in the present application can flexibly adjust the double bond content according to different application scenarios to adapt to different needs, while abandoning the traditional UV-curable polyurethane resin's dependence on diluents, further demonstrating its environmentally friendly characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] Figure 1 A schematic diagram of the chemical synthesis of a side double-bond itaconate polyol provided in Example 1 of the present application;
[0022] Figure 2 The infrared spectrum of the UV-curable polyurethane provided in the embodiment of the present application;
[0023] Figure 3 This is the infrared spectrum of propyl glycidyl ester before and after the reaction provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0024] The technical solutions of the embodiments of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the specification of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection requested by the present application.
[0025] The sources of all raw materials in the present invention are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0026] The embodiment of the present invention provides a method for preparing a lateral double-bond itaconate polyol, comprising the following steps:
[0027] Step S1, 60-70 parts of itaconic acid, 100-120 parts of allyl glycidyl ether, 0.08-0.15 parts of a catalyst and 0.08-0.15 parts of a polymerization inhibitor are mixed uniformly in an inert gas atmosphere, and kept warm for reaction at 95°C-110°C for 1.5-2 hours to obtain a crude product;
[0028] Step S2, taking the crude product and distilling it under reduced pressure at 100-110° C. for 0.5-1 h to obtain itacon polyol with a side double bond.
[0029] It should be noted that the side double-bond itaconic polyol provided in this embodiment uses itaconic acid and allyl glycidyl ether as reaction substrates, which effectively inhibits the loss of double bonds during the preparation process, so that the double bond retention rate is maintained at a high level (see Figure 1 The structural formula of the lateral double-bond itacon polyol is provided). By adding the lateral double-bond itacon polyol rich in double bonds to the UV-curable polyurethane resin, the content of double bonds in the UV-curable polyurethane resin can be significantly adjusted by only slightly adjusting the dosage of the lateral double-bond itacon polyol, so that the resin can be applied to a variety of different fields.
[0030] In some embodiments, the catalyst includes one of tetrabutylammonium bromide, benzyltriethylammonium chloride, triphenylamine, triethylamine, tributylamine, and the like.
[0031] In some embodiments, the polymerization inhibitor includes a phenolic polymerization inhibitor and a quinone polymerization inhibitor; the phenolic polymerization inhibitor includes one of p-methoxyphenol and hydroquinone; the quinone polymerization inhibitor includes one of p-benzoquinone and tetrachlorobenzoquinone.
[0032] The embodiment of the present invention provides a UV-curable polyurethane resin, comprising 99.5-99.9 parts of polyurethane resin and 0.1-0.5 parts of photoinitiator;
[0033] The polyurethane resin is composed of the following components in parts by mass: 40-80 parts of oligomer polyol; 5-25 parts of lateral double-bond itacon polyol prepared according to any one of claims 1 to 3; 10-30 parts of isocyanate; 0.1-1 parts of catalyst; 0.1-1 parts of inhibitor; 3-4 parts of end-capping agent; and 30-50 parts of solvent.
[0034] It should be noted that the introduction of a large number of lateral double-bond itacon polyols containing unsaturated carbon double bonds provides more active sites for photocrosslinking reaction for UV-curable polyurethanes. That is, under UV irradiation, the unsaturated groups between the polyurethane segments are cleaved by the photoinitiator to generate free radicals, which initiate free radical polymerization and crosslink the system. Therefore, the dosage of lateral double-bond itacon polyols is crucial to the reaction activity and crosslinking degree of UV-curable polyurethanes. Furthermore, in the component regulation and preparation process of UV-curable polyurethanes, the proportion of lateral double-bond itacon polyols in the raw materials can be flexibly adjusted and different types of oligomer polyols can be adapted to obtain UV-curable polyurethanes with different properties to meet the requirements of different application scenarios. See. Figure 2 In the figure, the PU-1 and PU-2 curves correspond to the UV-curable polyurethane based on polyester polyols and the UV-curable polyurethane based on polyethers, respectively. The UV-curable polyurethane based on polyester polyols has a peak at 1700 cm -1 The characteristic peak signal of the ester group near (corresponding to the double carbon functional group) is stronger, while the characteristic peak signal of the polyether UV-curable polyurethane is at 1100cm -1 Obvious ether characteristic peaks were obtained nearby.
[0035] It is necessary to further explain that the preparation steps of UV-curable polyurethane resin are as follows: Step S1, mix the oligomer polyol, the side double-bond polyol, the isocyanate, the catalyst, the inhibitor, and the solvent evenly, and keep the reaction at 80~95 ℃ for 4~6 hours; Step S2, add the end-capping agent after the reaction is completed and continue to keep the reaction for 0.5~1 hour to obtain the polyurethane resin. Step S3, take the polyurethane resin and the photoinitiator, mix them evenly, and then stand and degas to obtain the UV-curable polyurethane resin. In the application of UV-curable polyurethane resin, the components and preparation steps can be adaptively adjusted on the basis of the UV-curable polyurethane resin according to its application field to meet the needs of different application fields.
[0036] In some embodiments, the oligomer polyol includes one or more of polybutylene adipate diol, polypropylene carbonate diol, polypropylene glycol, and polycaprolactone diol.
[0037] In some embodiments, the isocyanate includes one or more of isophorone diisocyanate, diphenylmethane diisocyanate, meta-xylylene diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate.
[0038] In some embodiments, the solvent includes one or more of ethyl acetate, dimethylformamide, toluene, acetone, and tetrahydrofuran.
[0039] In some embodiments, the capping agent includes one or more of ethanol, n-propanol, hydroxyethyl acrylate, and hydroxyethyl methacrylate.
[0040] In some embodiments, the catalyst includes one or more of stannous isooctanoate and stannous octoate.
[0041] This embodiment provides an application of a UV-curable polyurethane resin for preparing a UV viscosity-reducing adhesive, a UV-curable coating, and a UV-curable electronic packaging adhesive.
[0042] It should be noted that the application of UV de-viscosity adhesive specifically refers to the application in the processing of silicon wafers. For example, UV de-viscosity adhesive can provide sufficient adhesion to fix the wafer in the processes of wafer cutting and polishing. After the processing is completed, it can be de-viscosified by UV irradiation to facilitate the pickup of the processed devices. The peel force test of the prepared UV de-viscosity adhesive in this application scheme further proves this point. For example, the average peel force before illumination is as high as 24 N / 25 mm, and the average peel force after illumination is as low as 0.08 N / 25 mm. No residual adhesive appears in either the strong adhesion stage before illumination or the de-viscosity treatment stage after illumination. This means that the UV de-viscosity adhesive not only performs well in the regulation of adhesion, but also reaches an extremely high level in terms of material cleanliness. Secondly, the UV-cured coating prepared by the present application shows strong adhesion and can fit tightly to the base material, ensuring the stability of the coating under complex working conditions; and its surface hardness is quite high, with good scratch resistance, which can effectively resist external physical friction; at the same time, it has excellent wear resistance and performs outstandingly in wear tests, greatly extending the service life of the coating. In addition, the UV electronic packaging glue prepared by the present application has extremely strong bonding properties and can form a stable connection between electronic components and packaging shells; at the same time, it also has excellent heat resistance, and can maintain a good packaging state even in the high temperature environment generated by the long-term operation of electronic equipment; in addition, it has excellent water and oxygen barrier properties, which can effectively block the intrusion of external water vapor and oxygen, creating a stable and dry internal environment for electronic components.
[0043] The applicant further provides the following reference specific embodiments to describe the present invention. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0044] Example 1
[0045] See also Figure 1, the present application embodiment provides a method for preparing a side double-bond itacon polyol, which is as follows:
[0046] 65 parts of itaconic acid, 115 parts of allyl glycidyl ether, 0.9 parts of triphenylphosphine and 0.35 parts of p-methoxyphenol were added into a dry reactor equipped with a stirring device, a thermometer and good sealing performance by weight. Inert gas was introduced into the reactor to expel the air. The reactor was then heated to 95°C and kept at 95°C for 1 h. The temperature was then raised to 110°C and kept at this temperature for 1.5 h. Finally, the temperature was lowered to 95°C and the pressure was reduced at this temperature for 1 h to finally obtain the side double-bond itaconic polyol. The obtained side double-bond itaconic polyol was placed in a light-proof dry sealed container for standby use.
[0047] Example 2
[0048] This embodiment provides a UV-curable polyurethane resin and its application in UV viscosity-reducing adhesive.
[0049] In the first aspect, the composition of the UV curable polyurethane resin is as follows:
[0050] The UV curable polyurethane resin comprises 99.72 parts of polyurethane resin and 0.28 parts of photoinitiator (TPO-L).
[0051] Wherein, the polyurethane resin is composed of the following components in parts by mass:
[0052] The oligomer polyol is 50 parts of polybutylene adipate diol (molecular weight 1000); 18 parts of side double-bond itacon polyol (obtained in Example 1); the isocyanate is 25 parts of diphenylmethane diisocyanate; the catalyst is 0.3 parts of stannous isooctanoate; the end-capping agent is 2 parts of anhydrous ethanol; the inhibitor is 0.3 parts of p-methoxyphenol; and the solvent is 35 parts of ethyl acetate.
[0053] In the second aspect, this embodiment provides an application of a UV-curable polyurethane resin in a UV viscosity-reducing adhesive, and the specific application steps are as follows:
[0054] Step S1, mixing the oligomer polyol, the pendant double-bond itacon polyol, the isocyanate, the catalyst, the inhibitor, and the solvent, and reacting them at 85° C. for 4.5 hours;
[0055] Step S2, after the reaction is completed, a capping agent is added and the reaction is continued for 0.5 h to obtain a polyurethane resin;
[0056] Step S3, 99.72 parts of polyurethane resin and 0.28 parts of photoinitiator are mixed evenly, and allowed to stand for 30 minutes for degassing to obtain UV viscosity-reducing adhesive.
[0057] Test 1: Peeling test
[0058] The UV viscosity-reducing adhesive obtained in this example was coated on a 25 mm wide PET sample with a coating thickness of 30 μm. After coating, the sample was placed in an oven at 80°C for 30 min to remove the solvent, and then cooled in a dark place to obtain a test sample. A 180° peeling test was performed on the test sample before and after UV irradiation in accordance with GB / T 25256-2010. The test substrate was a SUS stainless steel plate, and the UV irradiation amount was 4.0 J / cm 2 .
[0059] Test results: The average peeling force before UV irradiation was 2409 g / 25 mm, and the average peeling force after UV irradiation was 8 g / 25 mm. No residual adhesive occurred in both the peeling tests before and after light irradiation. It can be seen that the UV viscosity-reducing adhesive provided in this embodiment has a strong bonding strength before UV curing, and has a significant viscosity-reducing effect after UV curing, which can meet the manufacturing process requirements of precision components such as semiconductors.
[0060] Comparative Example 1
[0061] This embodiment provides a UV viscosity-reducing adhesive, see Chinese patent CN118652657A.
[0062] The difference between this patent and Example 2 is that a macromolecular dimer acid is used as a raw material and xylene is used as a solvent to react with allyl glycidyl ester at 130-160°C, and then the reaction product is reacted with diisocyanate as a soft segment and chain extended with a small molecule diol to obtain a UV viscosity-reducing adhesive.
[0063] However, this method takes a long time to react, and the double bonds on the allyl glycidyl ester will be lost due to the reaction at high temperatures, resulting in a high peeling force and poor viscosity reduction effect of the viscosity-reducing adhesive after light curing, which is not conducive to viscosity reduction after light curing. Figure 3 As shown in the figure, GMA-1 is the infrared spectrum curve of allyl glycidyl ester (GMA), and GMA-2 is the infrared spectrum curve of GMA prepared according to the scheme described in CN118652657A, with a wavelength of 1720 cm -1 The characteristic peak at was used as the reference peak, and the double bond loss before and after the treatment was analyzed by the internal standard method. The results showed that the double bond loss rate of GMA after the reaction was as high as 22.69%, which would significantly reduce the viscosity reduction of the adhesive after light curing. Based on the existing theoretical basis, if this scheme is to reduce the peel force after light curing and enhance the viscosity reduction after light curing, it can only increase the molecular weight or the soft segment content to increase the double bond content in the polyurethane. However, since the molecular weight of the adhesive is generally within a narrow range, if the soft segment content is increased, the cohesive energy of the adhesive will be reduced, making the bonding performance before light irradiation worse. Therefore, the polyurethane synthesized by this scheme is difficult to balance the characteristics of "strong bonding before light irradiation and viscosity reduction after light curing".
[0064] Combining the data effects of Example 2 and Comparative Example 1, it can be found that the side double-bond itaconic polyol prepared in the present application uses itaconic acid and allyl glycidyl ether as reaction substrates, which effectively inhibits the loss of double bonds in the preparation process, and maintains its double bond retention rate at a high level. This side double-bond itaconic polyol rich in double bonds is added to the UV-curable polyurethane resin. The content of double bonds in the UV-curable polyurethane resin can be significantly adjusted by only finely adjusting the dosage of the side double-bond itaconic polyol, and it is not easy to have the phenomenon of "reducing the cohesive energy of the adhesive in order to increase the soft segment content, resulting in a decrease in the bonding ability of the adhesive before illumination". Therefore, the UV-curable polyurethane resin containing side double-bond itacon polyol provided in the present application not only has strong bonding ability before illumination, but also has better viscosity reduction performance in the later photocuring stage, and can take into account the characteristics of "strong bonding before illumination and viscosity reduction after photocuring". The UV-curable polyurethane resin provided in the present application can not only be applied to the technical field of UV viscosity-reducing adhesive, but also can be used to prepare UV-curable coatings and UV-curable electronic packaging adhesives. Please refer to Examples 3 to 4 for details.
[0065] Example 3
[0066] This embodiment provides a UV-curable polyurethane resin and application thereof in a UV-curable coating.
[0067] In the first aspect, the composition of the UV curable polyurethane resin is as follows:
[0068] The UV curable polyurethane resin comprises 99.78 parts of polyurethane resin and 0.22 parts of photoinitiator (TPO-L).
[0069] Wherein, the polyurethane resin is composed of the following components in parts by mass:
[0070] The oligomer polyol is 60 parts of polytetrahydrofuran (molecular weight 1000); 18 parts of side double-bond itacon polyol (obtained in Example 1); the isocyanate is 25 parts of diphenylmethane diisocyanate; the catalyst is 0.3 parts of stannous isooctanoate; the end-capping agent is 2 parts of anhydrous ethanol; the inhibitor is 0.3 parts of p-methoxyphenol; and the solvent is 35 parts of ethyl acetate.
[0071] In a second aspect, this embodiment provides an application of a UV-curable polyurethane resin in a UV-curable coating, and the specific application steps are as follows:
[0072] Step S1, mixing the oligomer polyol, the pendant double-bond itacon polyol, the isocyanate, the catalyst, the inhibitor, and the solvent, and reacting them at 85° C. for 4.5 h;
[0073] Step S2, after the reaction is completed, a capping agent is added and the reaction is continued for 0.5 h to obtain a polyurethane resin;
[0074] Step S3, 99.72 parts of polyurethane resin and 0.28 parts of photoinitiator are mixed evenly, and allowed to stand for 30 minutes for degassing to obtain a UV curing coating raw material.
[0075] UV curing coatings were prepared using UV curing coating raw materials, and their physical and chemical properties were tested:
[0076] Preparation of UV-curing coating: Test-grade tinplate was selected and polished in horizontal and vertical directions with 400-mesh and 600-mesh sandpaper respectively. After polishing, it was wiped clean with ethyl acetate and dried. Then, the prepared UV-curing coating raw material was coated on the surface-treated tinplate with an applicator with a coating thickness of 60 μm. After coating, it was placed in an oven at 80°C for 30 min to remove the solvent, then cooled in a light-proof place, and finally cured by UV irradiation to obtain a UV-curing coating.
[0077] Test 1: Paint film adhesion test and pencil hardness test
[0078] According to the test process specified in GB / T 9286-2021, the adhesion of UV-cured coatings is accurately evaluated. The cross-hatch method is used, and the gap between the cross-hatch is precisely set to 2 mm to simulate the external force tearing situation that the coating may encounter in actual application.
[0079] After testing, the adhesion rating of the UV-cured coating can reach the Level 1 standard, which indicates that the coating has extremely strong adhesion to the base material. Even under complex working conditions, the coating has strong stability and can effectively resist damage to the integrity of the coating caused by external environmental factors.
[0080] The pencil hardness test was carried out in accordance with standard GB / T 6739-2022, and the test result was 4H.
[0081] Test 2: Paint film wear resistance
[0082] According to the established standard process of GB / T 1768-2006, the wear resistance test of UV-cured coating was carried out systematically. The BGD-523 / S paint abrasion tester with high-precision detection capability was selected as the test instrument. In the parameter setting stage, the load was adjusted to 750 g, the speed was stabilized at 60 r / min, and the number of wear circles was set to 500 circles, so as to accurately simulate the friction and wear conditions faced by the coating in actual use.
[0083] After testing, the final sample lost 73 mg in weight. This fully demonstrates that UV-curable polyurethane resin can be used in photocurable coatings and also has good wear resistance.
[0084] Example 4
[0085] The present embodiment provides a UV-curable polyurethane resin and a preparation method thereof and an application thereof in UV-curable electronic packaging adhesive.
[0086] In the first aspect, the composition of the UV curable polyurethane resin is as follows:
[0087] The UV curable polyurethane resin comprises 99.72 parts of polyurethane resin and 0.28 parts of photoinitiator (TPO-L).
[0088] Wherein, the polyurethane resin is composed of the following components in parts by mass:
[0089] The oligomer polyol is 80 parts of polytetrahydrofuran (molecular weight 1000); 8 parts of lateral double-bond itacon polyol (obtained in Example 1); 25 parts of diphenylmethane diisocyanate iso ...
[0090] In a second aspect, this embodiment provides an application of a UV-curable polyurethane resin in a UV-curable electronic packaging adhesive, and the specific application steps are as follows:
[0091] Step S1, mixing the oligomer polyol, the pendant double-bond itacon polyol, the isocyanate, the catalyst, the inhibitor, and the solvent, and reacting them at 85° C. for 5 h;
[0092] Step S2, taking 99.8 parts of polyurethane resin, 0.2 parts of photoinitiator (TPO-L), 5 parts of dipropylene glycol dibenzoate plasticizer and 3 parts of TDI modified blocked polyisocyanate curing agent (S-860N) and mixing them evenly, and then standing in a cool place for 30 minutes to remove bubbles, to obtain UV curing electronic packaging adhesive.
[0093] The UV-curable electronic packaging adhesive prepared above was used to prepare a cured sample to test its physical and chemical properties:
[0094] Preparation of cured samples: Pour about 20 g of UV-curable electronic packaging glue into a transparent plastic cup mold and bake it in an 80 °C oven for 50 min to remove the solvent for pre-curing. Then cool it in a dark place, and then cure it with UV irradiation and open the mold to obtain a cured block sample.
[0095] Test 1: Heat resistance test
[0096] In this experiment, a small amount of solidified block samples were taken and their heat resistance properties were accurately tested using a thermogravimetric analyzer (TGA). The nitrogen protection mode was turned on throughout the test, the heating rate was accurately controlled at 10 ℃ / min, and the scanning temperature range was set to 25~500 ℃, fully and carefully capturing the thermal weight loss behavior of the sample at different temperature nodes.
[0097] The experimental data clearly shows that the sample did not lose weight significantly until 260°C. This fully proves that when UV-curable polyurethane resin is used in the field of UV-curable electronic packaging adhesive, it has excellent heat resistance and can effectively reduce the risk of failure of electronic components due to overheating.
[0098] Test 2: Electrical performance test
[0099] This experiment uses a 6517 B-type high resistance meter, and carries out relevant testing work in accordance with GB / T 31838.2-2019.
[0100] The volume resistivity of the sample was measured to be This indicates that the UV-curable polyurethane resin provided in the present application has excellent insulation performance when applied to UV-curable electronic packaging adhesive, and can improve the insulation effect between electronic components.
[0101] Test 3: Barrier test
[0102] This experiment uses the W301 water vapor transmission rate meter with high-precision detection capabilities, and conducts relevant tests in accordance with GB / T1037-2021, Determination of water vapor transmission performance of plastic films and sheets: Cup weight gain and weight loss method. During the test, the experimental temperature was stabilized at 23.5 ℃ and the relative humidity was controlled at 90% to ensure the standardization and consistency of the test conditions.
[0103] The thickness of the solidified block sample tested was 120 μm, and the penetration area was set to 50 cm 2 Finally, the water vapor transmission rate of the sample was measured as follows: This indicates that the UV-curable polyurethane resin provided in the present application has excellent water vapor barrier properties when applied to the field of UV-curable electronic packaging adhesives, and can effectively block the intrusion of external water vapor and create a stable and dry internal environment for electronic components.
[0104] The above are only preferred embodiments of the present application and are not intended to limit the present invention. Although the present application has been described in detail with reference to the examples, those skilled in the art can still modify the technical solutions recorded in the aforementioned examples or make equivalent substitutions for some of the technical features therein. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a side double-bond itaconate polyol, characterized in that: The following steps are involved: Step S1, 60-70 parts of itaconic acid, 100-120 parts of allyl glycidyl ether, 0.08-0.15 parts of a catalyst and 0.08-0.15 parts of a polymerization inhibitor are mixed uniformly in an inert gas atmosphere, and kept warm for reaction at 95°C-110°C for 1.5-2 hours to obtain a crude product; Step S2, taking the crude product and distilling it under reduced pressure at 100-110° C. for 0.5-1 h to obtain itacon polyol with a side double bond.
2. The method for preparing the lateral double-bond itacon polyol according to claim 1, characterized in that: The catalyst comprises one of tetrabutylammonium bromide, benzyltriethylammonium chloride, triphenylamine, triethylamine and tributylamine.
3. The method for preparing the side double-bond itacon polyol according to claim 1, characterized in that: The polymerization inhibitors include phenolic polymerization inhibitors and quinone polymerization inhibitors. The phenolic polymerization inhibitor includes one of p-methoxyphenol and hydroquinone; the quinone polymerization inhibitor includes one of p-benzoquinone and tetrachlorobenzoquinone.
4. A UV curable polyurethane resin, characterized in that: It includes 99.5-99.9 parts of polyurethane resin and 0.1-0.5 parts of photoinitiator; The polyurethane resin is composed of the following components in parts by mass: 40 to 80 parts of oligomer polyol; 5 to 25 parts of the side double-bond itacon polyol prepared according to any one of claims 1 to 3; 10 to 30 parts of isocyanate; 0.1 to 1 part of catalyst; 0.1 to 1 part of inhibitor; 3 to 4 parts of end-capping agent; and 30 to 50 parts of solvent.
5. The UV-curable polyurethane resin according to claim 4, characterized in that The oligomer polyol includes one or more of polybutylene adipate diol, polypropylene carbonate diol, polypropylene glycol and polycaprolactone diol.
6. The UV-curable polyurethane resin according to claim 4, characterized in that The isocyanate includes one or more of isophorone diisocyanate, diphenylmethane diisocyanate, meta-xylylene diisocyanate, toluene diisocyanate, hexamethylene diisocyanate and dicyclohexylmethane diisocyanate.
7. The UV-curable polyurethane resin according to claim 4, characterized in that The solvent includes one or more of ethyl acetate, dimethylformamide, toluene, acetone and tetrahydrofuran.
8. The UV-curable polyurethane resin according to claim 4, characterized in that The end-capping agent includes one or more of ethanol, n-propanol, hydroxyethyl acrylate and hydroxyethyl methacrylate.
9. The UV curable polyurethane resin according to claim 4, characterized in that The catalyst includes one or more of stannous isooctanoate and stannous octoate.
10. Use of the UV curable polyurethane resin according to any one of claims 4 to 9, characterized in that: Used to prepare UV viscosity-reducing adhesives, UV curing coatings, and UV curing electronic packaging adhesives.
Citation Information
Patent Citations
Polyurethane type UV viscosity-reducing adhesive based on dimer acid and preparation method of polyurethane type UV viscosity-reducing adhesive
CN118652657A